Hubungan Usia dan Lama Puasa dengan Kejadian Hipotensi Pada Pasien dengan Anestesi Spinal di RSUD Kardinah Tegal - M Rizqy Diaz Alfarizi; Wilis Sukmaningtyas; Maya Safitri (Medika: Jurnal Ilmiah Kesehatan, 2025)
Hypotension is the most common complication that occurs following spinal anesthesia and can be influenced by various factors, including age and the duration of preoperative fasting. Untreated hypotension may lead to decreased tissue perfusion, reduced consciousness, organ ischemia, and even shock. This study aims to determine the relationship between age and fasting duration with the incidence of hypotension in patients undergoing spinal anesthesia at Kardinah Regional Hospital, Tegal. A quantitative approach was employed using a descriptive correlational design with a cross-sectional method. A total of 98 respondents were selected through purposive sampling. Data were collected using observation sheets and analyzed using the Chi-Square test. The results showed that the majority of respondents were in the 46–55 year age group (43.9%) and had fasted for more than 8 hours (58.2%). A total of 64.3% of respondents experienced hypotension after spinal anesthesia. Statistical analysis revealed a significant relationship between age and the incidence of hypotension (p = 0.000), as well as between fasting duration and the incidence of hypotension (p = 0.000). It can be concluded that the older the patient and the longer the fasting duration, the higher the risk of developing hypotension.